Free radical solution copolymerization of monomers of dissimilar reactivity - influencing chemical composition distribution and properties of copolymers of methyl methacrylate and N-vinyl imidazole by varying monomer feeding profiles. (28th April 2022) - Rusli, Wendy; Benjamin Tan, Song Wei; Parthiban, Anbanandam; van Herk, Alex M.
Abstract: Copolymerization is one way of influencing the properties of polymers and the outcome of copolymerization between vinyl monomers is dependent on the reactivity ratios between the monomers. Incorporation of polar monomers into copolymers offer many benefits. In this regard, N-Vinyl imidazole (NVI) carries much significance as a comonomer. NVI is a specialty monomer. The high polarity and planarity of NVI can impart many beneficial characteristics upon copolymerization with other vinyl monomers. However, its unfavourable reactivity ratios with other vinyl monomers prevent the facile incorporation of NVI in the copolymers. In this work, a semi-continuous solution polymerization is employed with the help of software called Monomer Addition Profile (MAP) to predict the optimal addition profile of the more reactive monomer (methyl methacrylate) through an iterative approach in order to achieve uniform incorporation of less reactive comonomer in the copolymer chain. The predicted chemical composition distribution (CCD) of the copolymerization is used to determine the homogeneity of copolymers which is well supported by the glass transition temperature ( T g ) of copolymers. Apart from the workflow of MAP, solubility characteristics of copolymers, microstructure and sequence length are also discussed in this article. Graphical abstract: Image 1 Highlights: Improved copolymerization using Optimal Monomer Addition Profile (OMAP) process. Copolymerization of vinyl monomers of unequal reactivity - MMA and N-Vinyl imidazole. Copolymers with improved chemical composition distribution. Incompatible copolymers with reduced glass transition temperature window. Enhanced solution transparency with improved homogeneity of copolymers.